2016
DOI: 10.1002/jsfa.7798
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of carotenoids, vitamin E and phenolic compounds in Provitamin A biofortified maize

Abstract: Genotype was significant in determining the variation in β-cryptoxanthin, β-carotene, α-tocopherol and γ-tocopherol contents (P < 0.01). A genotype × environment interaction was observed for γ-tocopherol content (P < 0.01). © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 35 publications
12
37
5
1
Order By: Relevance
“…However, none of these approaches had been viable due to ineffective distribution system, poor infrastructure and/or non‐affordability by the poor people (Tanumihardjo, Palacios‐Rojas, & Pixley, ). Biofortification, the process of breeding micronutrient dense staple crops, is cost‐effective, sustainable and micronutrients can be delivered among the target group in its natural form (Bouis & Welch, ; Gupta et al., ; Muzhingi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these approaches had been viable due to ineffective distribution system, poor infrastructure and/or non‐affordability by the poor people (Tanumihardjo, Palacios‐Rojas, & Pixley, ). Biofortification, the process of breeding micronutrient dense staple crops, is cost‐effective, sustainable and micronutrients can be delivered among the target group in its natural form (Bouis & Welch, ; Gupta et al., ; Muzhingi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Another research comprehends 87 inbred lines from the main heterotic groups in China and revealed βcarotene content in range from 0.016-1.726 µg/g DW (Chander et al, 2008), much lower than obtained in inbreds in our study. In maize hybrids biofortified for vitamin A (Kurilich and Juvik, 1999) β-carotene content was 0.55 µg/g DW, and in new 36 provitamin A biofortified hybrids (Muzhingi et al, 2017) β-carotene was within range from 1.3-8.00 µg/g DW. Provitamin A (α-carotene, β-carotene, βcryptoxanthin) and non-provitamin A carotenoids (lutein and zeaxanthin) in maize are primarly located in the endosperm, but tocopherols (α-tocopherol, γ-tocopherol and δ-tocopherol) are located in the embryo.…”
Section: Resultsmentioning
confidence: 94%
“…Higher carotenoid content could be estimated based on grain color, but not determineted, because of possible accumulation in different parts of maize kernel (seed coat, endosperm or germ). However, maize is not only a good source for provitamin A carotenoids but also a source of vitamin E, tocochromanols and phenolic compounds, which have antioxidant properties (Muzhingi et al, 2017). Vitamin E is common name for eight naturally occurring compounds, lipidsoluble antioxidants with two distinct groups, tocopherols and tocotrienols (Della Penna, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Wide genetic variation in tocopherol components has been observed in maize (Rocheford et al, 2002;Egesel et al, 2003;Li et al, 2012;Feng et al, 2015;Muzhingi et al, 2017;Das et al, 2019a). Estimation of tocopherol fractions (a-, b-, g-, and d-) is simple and fast (~15 min/sample) using HPLC, but it involves high cost (US$25-30 per sample).…”
Section: Molecular Breeding For Vitamin E Enrichmentmentioning
confidence: 99%